Lo spaesamento delle viaggiatrici europee al nord: Straniamenti odeporici - Patat, Ellen (Incontri. Rivista europea di studi italiani, 2021)
The displacement of European female Travellers in the North Estrangements in travel writingThe present paper focuses on the travel accounts written by four women who decided to visit the European North in mid- and late-Nineteenth century: Ida Laura Pfeiffer’s Visit to Iceland and Scandinavian North (1853), Carla Serena’s Mon voyage personnels: souvenirs De la Baltique à la Mer Caspienne (1881), Ethel Brianna Tweedies’ A girl’s ride in Iceland (1889), and Elisa Cappelli’s In Svezia. Impressioni di viaggio (1902). The aim is to analyse these travel diaries to identify the various forms of displacement and estrangement presented to the readers. The term ‘displacement’ is here to be understood as the condition of the ‘outsider’, the perception of being ‘the Other’, whereas ‘estrangement’ could be considered the reformulation of this awareness. This paper highlights real displacements that derive from social, cultural, geographical, and gender discrepancies adopting a comparative approach, which concentrates on the textual and semantic solutions, also taking into account the interdependence of travel and writing and of space and people. These aspects intertwine with the factual reality of the travel discourse, ultimately leading to both ‘literary’ and ‘existential’ estrangements.